Analisis Deskriptif Gaya Mengajar Guru PJOK serta Tingkat Kebugaran Aerobik (PACER Test) Siswa Kelas IX di SMP Negeri se-Kecamatan Wiyung Surabaya - Amalia Tazkiyah; Heryanto Nur Muhammad; Sri Wicahyani (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aims to describe the teaching styles of Physical Education, Sports, and Health (PJOK) teachers and the aerobic fitness levels of ninth-grade students based on the results of the PACER Test at public junior high schools in the Wiyung District of Surabaya. The study used a quantitative descriptive approach with research locations at Public Junior High Schools 34, 51, and 59 in Surabaya. The research subjects consisted of 85 ninth-grade students and three PJOK teachers selected using purposive sampling. The research instruments included a Likert scale questionnaire on PJOK teachers' teaching styles to identify teaching style tendencies and the PACER Test to measure students' aerobic fitness levels. The data were analyzed using descriptive statistics in the form of scores, percentages, and radar diagram visualizations. The results showed that the teaching styles of PE teachers at SMP Negeri 34 and SMP Negeri 51 were dominated by the command style, while those at SMP Negeri 59 tended to use the student-initiated style. However, the PACER Test results at all three schools showed that the majority of students were in the “very poor” aerobic fitness category. These findings indicate that differences in teaching styles have not been accompanied by optimal levels of students' aerobic fitness. Therefore, more varied PJOK learning is needed, oriented towards intensive physical activity and supported by students' physical activity habits outside of class hours.